Recent philosophy and the fiction/non-fiction distinction. (3rd April 2018) - Matravers, Derek
Abstract : Purpose: The purpose of this paper is to provide an overview of recent philosophical argument concerning the distinction between fiction and non-fiction. Design/methodology/approach: A critical view of the literature. Findings: A consensus that had emerged that defined fiction in terms of the imagination, and imagination in terms of its functional role, has recently been questioned. Research limitations/implications: The overview was written by a contributor to the field, and so may be considered partial. Practical implications: There might be some implications regarding the ways books are classified. Originality/value: The paper is not original, in that it puts forward points made elsewhere, however it is a completely up-to-date review of the field.